Library development strategy at SMP Negeri 9 Bandung through P3NK - Kania Azzahra Putri; Najwa Nurafifa; Rini Indriyani; Lutfi Khoerunnisa (Universitas Pendidikan Indonesia, 2025)
A library is an institution or work unit that has an essential role in providing access to information, education, research, and recreation for the community. This community service analyzes the library development strategy at SMP Negeri 9 Bandung through the implementation of the Non-Educational Professional Strengthening Program (P3NK). This program is designed to actively engage students in library management actively, enhancing service quality and the professionalism of library staff. Through student participation, the program also aims to introduce various innovations, improve operational efficiency, and enhance user-centered services. The research employed a qualitative descriptive method, with data collected through interviews, direct observation, and documentation studies. The findings revealed that the P3NK program successfully improved various aspects of library services, including collection management, digitization processes, and the development of literacy activities. The program also had a positive impact on enhancing the competencies of library staff, optimizing the use of technology, and creating a more interactive and conducive learning environment for students. Close collaboration between students, librarians, and teachers emerged as a key factor in the successful implementation of this program. The community services conclude that the P3NK program can serve as an effective strategic model for developing school libraries that are more dynamic, innovative, and aligned with the demands of education in the 21st-century digital era. Abstrak Perpustakaan adalah lembaga atau unit kerja yang memiliki peran penting dalam menyediakan akses terhadap informasi, pendidikan, penelitian, dan rekreasi bagi masyarakat. Pengabdian ini menganalisis strategi pengembangan perpustakaan di SMP Negeri 9 Bandung melalui implementasi Program Penguatan Profesional Non-Kependidikan (P3NK). Program ini dirancang untuk melibatkan peserta didik secara aktif dalam pengelolaan perpustakaan dengan tujuan meningkatkan kualitas layanan serta profesionalisme staf perpustakaan. Melalui partisipasi peserta didik, program ini juga bertujuan memperkenalkan berbagai inovasi, meningkatkan efisiensi operasional, dan memperkuat layanan berbasis kebutuhan pengguna. Metode pengabdian yang digunakan adalah deskriptif kualitatif, dengan data yang diperoleh melalui wawancara, observasi langsung, dan studi dokumentasi. Hasil pengabdian mengungkapkan bahwa Program P3NK berhasil meningkatkan berbagai aspek layanan perpustakaan, seperti manajemen koleksi, proses digitalisasi, dan pengembangan kegiatan literasi. Program ini juga berdampak positif terhadap peningkatan kompetensi staf perpustakaan, optimalisasi pemanfaatan teknologi, serta terciptanya lingkungan belajar yang interaktif dan kondusif bagi peserta didik. Kolaborasi erat antara peserta didik, pustakawan, dan pendidik menjadi faktor utama dalam keberhasilan implementasi program ini. Kesimpulan dari pengabdian ini adalah bahwa Program P3NK dapat dijadikan model strategis yang efektif untuk mengembangkan perpustakaan sekolah yang lebih dinamis, inovatif, dan relevan dengan tuntutan pendidikan di era digital abad ke-21. Kata Kunci: literasi peserta didik; manajemen perpustakaan; perpustakaan sekolah